Classification and regulatory interactions of key transcription factors in COVID-19 - Modipane, Ndimo; Mbambara, Saidon; Serite, Thato; Sathekge, Mike; Kgatle, Mankgopo (Frontiers in Cellular and Infection Microbiology, 2025)
SARS-CoV-2, the virus responsible for COVID-19, interferes with the host’s transcriptional control systems, triggering widespread disruption of immune regulation and metabolic stability. Key transcription factors (TFs), including AHR, NRF2, NF-κB, IRFs, HIF-1α, PARP, STAT3, ATF3, and PPARγ, play crucial roles in inflammation, oxidative stress defence, anti-viral responses, and immunometabolic adaptation. Their activity and interactions are modulated by post-translational modifications (PTMs) such as phosphorylation, SUMOylation, and ubiquitination, which shape COVID-19 progression. Specifically, SUMOylation of PPARγ suppresses NF-κB-driven inflammation, though impairment under severe disease amplifies macrophage activation and cytokine release. NRF2 degradation via KEAP1–CUL3–mediated ubiquitination is manipulated by the virus to deregulate oxidative stress responses, while SARS-CoV-2 also modulates NF-κB activity through ubiquitination of viral proteins (e.g., NSP6, ORF7a). Dynamic crosstalk between AHR and NRF2 further illustrates TF duality in detoxification and inflammation, with SUMOylation potentially influencing nuclear retention and transcriptional precision. This review classifies transcription factors into four functional categories: inflammatory regulators, antiviral response mediators, stress and pathogen response elements, and metabolic modulators. It further examines how PTM–driven crosstalk contributes to immune dysregulation. Targeting these transcriptional networks presents promising therapeutic strategies to mitigate hyperinflammation, rebalance immune responses, and enhance clinical outcomes in COVID-19.